PENGARUH EARNING PER SHARE DAN CASH RATIO TERHADAP DIVIDEN PAYOUT RATIO DENGAN ASSET GROWTH SEBAGAI VARIABEL MODERASI PADA SEKTOR INDUSTRI BARANG KONSUMSI DI BEI PERIODE 2009-2012 - Muhammad Hidayat (JURNAL DIMENSI, 2014)
This study is performed to examine the effect of Earning Per Share and Cash Ratio toward Dividend Payout Ratio with Asset Growth as a moderating variabel on companies which were consumer goods industry sector  listed in Indonesia Stock Exchange over period 2009-2012.Population of this research were 33 companies. Sample selected by using method of purposive sampling were 15 companies. The data research is secondary data obtained from the Indonesian Stock Exchange (www. idx.co.id). Hypothesis testing studies used linear regression analisys and moderated regression analysis, with application tool of SPSS (Statistical Product and Service Solutions).From the analysis result indicates that Earning Per Share variable partially significant positive toward Dividend Payout Ratio on the level of significance less than 5%, while it indicates that Cash Ratio variable not significant positive toward Dividen Payout Ratio. Asset Growth is not able to significantly moderate the effect of Earning Per Share on the Dividend Payout Ratio, Asset Growth is not able to significantly moderate the effect of Cash Ratio on the Dividend Payout Ratio.